2021
DOI: 10.1002/jqs.3385
|View full text |Cite
|
Sign up to set email alerts
|

Determining the diagenetic paths of archaeofaunal assemblages and their palaeoecology through artificial intelligence: an application to Oldowan sites from Olduvai Gorge (Tanzania)

Abstract: The implementation of deep‐learning methods to the taphonomic analysis of the microscopic modification of bone‐surface modifications exposed to different chemical diagenetic pathways can effectively discriminate between acidic and alkaline soil properties, indirectly reflecting different ecological conditions. Here we use this novel method to assess the sedimentary conditions of two of the oldest Oldowan archaeofaunal records (DS and PTK, Bed I) from Olduvai Gorge Bed I in Tanzania. We show how the results sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Artificial intelligence can help users get better services, but it also can further reflect the value of the users themselves to help them get a better experience. Literature [22] used artificial intelligence technology to carry out a micro-analysis of the pathway of petrogenesis of the Ordovan ancient volcano, which can realize the differentiation of the acidity and alkalinity of the volcanic soil and help people to understand the development of the volcano under different petrogenetic conditions. Literature [23] proposed a regression model based on artificial intelligence techniques to estimate stellar masses, and 726 MS planet samples were used for validation and the results showed that the model can realize effective tracking of planets.…”
Section: ) Artificial Intelligencementioning
confidence: 99%
“…Artificial intelligence can help users get better services, but it also can further reflect the value of the users themselves to help them get a better experience. Literature [22] used artificial intelligence technology to carry out a micro-analysis of the pathway of petrogenesis of the Ordovan ancient volcano, which can realize the differentiation of the acidity and alkalinity of the volcanic soil and help people to understand the development of the volcano under different petrogenetic conditions. Literature [23] proposed a regression model based on artificial intelligence techniques to estimate stellar masses, and 726 MS planet samples were used for validation and the results showed that the model can realize effective tracking of planets.…”
Section: ) Artificial Intelligencementioning
confidence: 99%